– 2X = a – b
Let’s divide both sides of the equation by -2
To make your result more beautiful, you can multiply the numerator and the denominator by – 1.
The next equation:
3a – 6X = 6X – 9a
You can see that on the left side of the equation you have -6X
and on the right side +6X. It is more convenient for you to have a + in front of X, therefore, you leave +6X on the right side and get rid of -6X on the left side of the equation.
Add 6X to both sides of the equation:
3a – 6X +6X = 6X – 9a +6X then 3a = 12X – 9a
Add 9a to both sides of the equation:
3a +9a = 12X – 9a +9a then 12a = 12X
X = a
Do not read any more until you perform some exercises.
Practice 3. Solving the equations
Answers: page 20
Solutions: page 27
(Solve for X)
1. 1 – X = 5 – a
2. 1 – 2X = X – 4
3. a – 3X = b – X
4. 2a – 4X = 2X – 4a
5. 4b – 2X = 2X – 4b
6. ab + aX = 2aX + ac
7. ab + aX = 2aX – ac
Let us continue and discuss the equation: aX – bX = a – b
Factor out X which is a common factor for binomial aX – bX,
then you will get X (a – b) = a – b
Divide each part of the equation by a – b
X (a – b) / (a – b) = (a – b) / (a – b)
X = 1
Do not read any more until you perform some exercises.
Practice 4. Solving the equations
Answers: page 20
Solutions: page 30
(Solve for X)
1. bX – 2b = aX – 2a
2. b – 2bX = a – 2aX
3. aX – bX = 1
4. aX – bX – cX = 2a – 2b – 2c
5. 3abX – 5a = 3acX +13a
6. aX – bX = ac – bc
7. 9a – 4X = 5a – 2X
8. X – aX = 2 – 2a
9. aX – bX = b – a
Let us continue and solve the equation: aX – bX = 2b – 2a
Factor out X from the left side of the equation.
X (a – b) = 2b – 2a
Factor out 2 from the right side of the equation.
X (a – b) = 2 (b – a) then divide both sides by (a – b)
Factor out (-1) from the denominator
Or you can simplify this algebraic expression by factoring out (-1) from the numerator
Practice 5. Solving the equations
Answers: page 20
Solutions: page 32
Solve for X.
1. 5aX – 5bX = 10b – 10a
2. aX – bX – cX = c + b – a
3. 2X – 3aX = 6a – 4
4. 3aX – 9bX = 27b – 9a
5. 4bX – cX = 8c – 32b
6. abX – acX = ac – ab
7. X/2 – aX = 1 – 2a
8. aX/5 +2a = 5a – 4aX
You can find answers in appendix 1 and solutions in appendix 2.
2. SYSTEM OF EQUATIONS
Look at the equation X + Y = 3. X and Y are unknown. You cańt find neither X nor Y from this equation. You need additional information about the “relationship” between them. Such information may be included in an additional equation. For example: X – Y = – 1. Now you have a system of 2 equations:
1. X + Y = 3
X – Y = -1
There are several ways to solve it. The first way: solve for X in any equation, for example, the first one.
In order to do that, subtract Y from each side of the equation:
X + Y – Y = 3 – Y; Find X
X = 3 – Y
Then put (3 – Y) in place of X in the second equation (X – Y = -1).
You will obtain: 3 – Y – Y = -1 or 3 – 2Y = -1
Now solve that equation for Y. Add 2Y to
3 – 2Y +2Y = -1 +2Y
3 = -1 +2Y
Add 1 to the both sides of the equation.
3 +1 = -1 +1 +2Y
4 = 2Y
Конец ознакомительного фрагмента.
Текст предоставлен ООО «ЛитРес».
Прочитайте эту книгу целиком, купив полную легальную версию на ЛитРес.
Безопасно оплатить книгу можно банковской картой Visa, MasterCard, Maestro, со счета мобильного телефона, с платежного терминала, в салоне МТС или Связной, через PayPal, WebMoney, Яндекс.Деньги, QIWI Кошелек, бонусными картами или другим удобным Вам способом.